MEASUREMENT AND MODELLING OF SORPTION EQUILIBRIUM CURVE OF WATER ON PA6, PP, HDPE AND PVC BY USING FLORY-HUGGINS MODEL - Suherman Suherman; Mirko Peglow; Evangelos Tsotsas (Dept. of Chemical Engineering, Diponegoro University, 2010)
The sorption of water on granular polyamide-6 (PA6), granular polypropylene (PP), and powdery high density polyethylene (HDPE) and powdery polyvinyl chloride (PVC) were measured using a gravimetric method in a magnetic suspension balance (MSB). The Flory-Huggins model was successfully applied on the sorption equilibrium curve of all investigated polymers. The influence of temperature is low. The value of Flory-Huggins parameters(c) of PA6, PVC, PP and HDPE were 1.8, 5.8, 6.3, and 8.1, respectively. The water in PA6 is mainly bound moisture, while in PP, HDPE and PVC it is mainly surface moisture.